Investigation of enhanced Fenton process (EFP) in color and COD removal of wastewater containing Acid Red 18 by response surface methodology: evaluation of EFP as post treatment. Issue 30 (26th June 2016) - Azizi, Armineh; Alavi Moghaddam, Mohammad Reza; Maknoon, Reza; Kowsari, Elaheh
Abstract: The purpose of this study was to investigate the application of enhanced Fenton process (EFP) using zero-valent iron combined with ultrasonic irradiation for treatment of wastewater containing acid red 18 (AR18) by response surface methodology. According to the analysis of variance results, the model presents high R 2 -value of 98.2 and 98.3% for the COD and AR18 dye removal, respectively, indicating that the model was successful. In this paper, the results of the monitoring of oxidation reduction potential and dissolved oxygen were presented to obtain the reaction time. At the 60 min of contact time, AR18 dye and COD removal efficiency raised more than 30 and 5% with the increase in Fenton reagents, respectively. Effluent without the presence of phosphate indicated 40% increment of AR18 dye removal in comparison to the influent with the presence of phosphate. Considering the EFP as post treatment of a sequencing batch reactor, the combination system improved the efficiency of high azo dye AR18 concentration wastewater treatment.